Escritura Colaborativa Digital en los Semilleros de Investigación para la Formación en Literacidades - Abad Olaya, José Vicente; Uribe Zapata, Alejandro (Colombian Applied Linguistics Journal, 2023)
The pedagogical innovation herein described, which emerges within the framework of research education, seeks to articulate digital collaborative writing between teacher educators and student teachers. The text consists of four parts. With the background of research training in teacher education, we first outline academic and digital literacies, which serve to theoretically scaffold the proposal. The second part explores its core categories: research seedbeds, collaborative writing, and digital writing. Then, the exercise of collaborative writing between teacher educators and student teachers is described considering methodological aspects that have served to implement it and that can guide its subsequent evolution, particularly in relation to multimodality. We conclude that collaborative writing as a pedagogical strategy has not been sufficiently investigated, yet it may contribute to the preparation of new researchers as it focuses on the development of academic and digital literacies.